1988
DOI: 10.1172/jci113391
|View full text |Cite
|
Sign up to set email alerts
|

Use of human surfactant low molecular weight apoproteins in the reconstitution of surfactant biologic activity.

Abstract: Two low molecular weight (LMW) apoproteins were isolated from human pulmonary surfactant. SDS polyacrylamide gel analysis showed one protein (SP 18) to have an apparent molecular weight of 18,000 when unreduced and 9,000 D after reduction. The second protein (SP 9) migrated at -9,000 D in the presence or absence of reducing agents. Both proteins contain a high number of hydrophobic amino acids. The NH2-terminal sequence of SP 18 was determined to be: NH2-phe-proile-pro-leu-pro-tyr-. A cDNA clone isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(64 citation statements)
references
References 52 publications
(67 reference statements)
2
61
0
1
Order By: Relevance
“…Survanta has an SP-B content by ELISA of only 0.044% by weight relative to phospholipid, while CLSE (Infasurf®) has an SP-B content of 0.9% by weight that approaches that of lavaged whole surfactant [118]. SP-B is known to be the most active of the hydrophobic surfactant proteins in enhancing the adsorption, dynamic surface activity, and inhibition resistance of phospholipids [118,[176][177][178][179][180][181][182][183][184]. The addition of bovine SP-B or synthetic SP-B peptides to Survanta® significantly improves its surface and physiological activity towards that of Infasurf and whole surfactant [106,118,175] (Figure 5)‥ Despite its lack of SP-B, other active components such as SP-C in Survanta® allow it to have significant efficacy in some forms of ALI/ARDS as noted earlier (e.g., [130,131,133]).…”
Section: Activity and Inhibition Resistance Of Exogenous Surfactant Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Survanta has an SP-B content by ELISA of only 0.044% by weight relative to phospholipid, while CLSE (Infasurf®) has an SP-B content of 0.9% by weight that approaches that of lavaged whole surfactant [118]. SP-B is known to be the most active of the hydrophobic surfactant proteins in enhancing the adsorption, dynamic surface activity, and inhibition resistance of phospholipids [118,[176][177][178][179][180][181][182][183][184]. The addition of bovine SP-B or synthetic SP-B peptides to Survanta® significantly improves its surface and physiological activity towards that of Infasurf and whole surfactant [106,118,175] (Figure 5)‥ Despite its lack of SP-B, other active components such as SP-C in Survanta® allow it to have significant efficacy in some forms of ALI/ARDS as noted earlier (e.g., [130,131,133]).…”
Section: Activity and Inhibition Resistance Of Exogenous Surfactant Dmentioning
confidence: 99%
“…However, the 21 amino acid KL4 peptide is only a very rough structural analog to native SP-B, and advances in peptide molecular modeling and synthesis technology support the feasibility of preparing new SP-B peptides with significantly greater sequence and molecular folding specificity, and correspondingly higher activity ( [202][203][204] for review). The development of new synthetic SP-B peptides is particularly important for optimal synthetic exogenous surfactants given the greater activity of SP-B compared to SP-C in native surfactant noted earlier [118,[176][177][178][179][180][181][182][183][184]. In addition to peptide/protein components in new synthetic surfactants, it is also important to consider their lipid constituents.…”
Section: Examples Of Research On New Synthetic Exogenous Surfactamentioning
confidence: 99%
“…SP-B was isolated from human amniotic fluid surfactant ad escribed previously (10). One hundred J.Lg of SP-B, in a volume of 206 J.LL methanol, were incubated with 5.14 mg DTT (Sigma Chemical Co, St. Louis, MO) in 17 J.LL methanol, for 1 h at 37°C.…”
Section: Preparation Ofpurified Sp-b Monomer Dimer and Oligomersmentioning
confidence: 99%
“…Our previous studies (10) and those of Curstedt et al (2), and Yu and Possmayer (19), suggested that when recombined with PL, SP-B resulted in greater surface tension lowering and biologic activity than did SP-C. For this reason, we decided to focus our attention on this protein. SP-B, also called SP-18 (4,10), SPL(Phe) (3), PSP-B (5), and SAP-6-14 (7,16,17,23), has been shown to be a disulfide-linked dimer of two identical polypeptides of approximately 9000 D having an amino terminal sequence of phe-pro-ile-pro-leu-pro-tyr-(human) (3,5,10).…”
mentioning
confidence: 98%
See 1 more Smart Citation